Immigrants and the Western media: a critical discourse analysis of newspaper framings of African immigrant parenting in Canada. Issue 19 (15th December 2021) - Alaazi, Dominic A.; Ahola, Alphonse Ndem; Okeke-Ihejirika, Philomina; Yohani, Sophie; Vallianatos, Helen; Salami, Bukola
ABSTRACT: In this paper, we utilised a critical discourse analysis methodology to highlight the discursive representation of African immigrant parenting in Canadian newspapers. We explored unquestioned ideologies and assumptions about African immigrant families and their parenting practices. We analysed 37 newspaper articles, after screening 635 records retrieved from the Canadian Newsstand database. Our analysis revealed discursive patterns that: (1) reflect unequal power relations and reinforce popular stereotypes about African immigrant families in Canada; (2) pathologize, demonise, and present a monolithic view of African immigrant parenting; and (3) influence service providers and institutional practices in ways that affect the parenting success of African immigrants. We also found a tendency to problematise African immigrant families and frame their parenting practices as being inferior to Canadian parenting practices and value systems. We argue that this grim representation of African immigrant parenting is a manifestation of power, cultural, and ideological differences, some of which are rooted in the immediate colonial past. We present policy and service implications of our findings, including a call for cultural education for Canadian service agencies.